Muscles : our muscular system - Simon, Seymour ([New York] : HarperCollins, 1998)
Describes the nature and work of muscles, the different kinds, and the effects of exercise and other activities on them.
Elem. School Library Collection
Wilson's Children
Wilson's Junior High School
Booklist, September 1998
Bulletin (Center for Children's books), September 1998
Christian Library, September 2000
Keywords: Muscles -- Juvenile literature; Musculoskeletal system -- Juvenile literature; Muscles; Muscular system; Muscles; Musculoskeletal system